Students' Ability to Develop Sentences in English Writing - Sam Hermansyah; M Hijaz Tahir; Agus Hambing; Roni (International Journal of Sustainable Applied Sciences, 2023)
This study focuses on analyzing students' ability to develop paragraphs through the number of sentences, quality or understandability of paragraphs by analyzing the unity and coherence of sentences. This study is a quantitative-qualitative study. The research subjects are students in the 5th semester of the English program. The data collection tool is an experiment. Quantitative data were analyzed using the frequency formula, and qualitative data on sentence unity and coherence were analyzed  using coding. Thus, the results show that  most students can write two to three sentences in a paragraph. Paragraphs consisting of one sentence and two sentences are rated as poor paragraphs. Paragraphs consisting of four, five, six and seven sentences are considered to be quite good paragraphs; and the paragraph consisting of three and eight sentences was marked as a good paragraph.